Vitamin D deficiency is a risk factor for infections in patients affected by HCV-related liver cirrhosis. (October 2017) - Buonomo, Antonio Riccardo; Zappulo, Emanuela; Scotto, Riccardo; Pinchera, Biagio; Perruolo, Giuseppe; Formisano, Pietro; Borgia, Guglielmo; Gentile, Ivan
Abstract: Objectives: To evaluate the prevalence of vitamin D deficiency and its impact on infections in HCV-related liver cirrhosis. Methods: We enrolled 291 patients affected by HCV-related liver cirrhosis. Serum vitamin D levels were dosed at enrolment. The presence of infection was assessed at baseline and during follow-up based on physical examination and laboratory analyses. Results: Vitamin D deficiency (<20 ng/mL) was diagnosed in 68.3% of patients, and a total of 102 infections were detected. Urinary tract infections were the most common infections diagnosed (41.2%). Vitamin D deficiency rates were higher in patients with decompensated cirrhosis (Child-Pugh B vs A p = 0.008, and Child-Pugh C vs A p = 0.024). Infection was significantly associated with vitamin D deficiency (p < 0.001), MELD score >15 (p = 0.003), Child-Pugh class B/C vs A (p < 0.001), and active hepatocellular carcinoma (HCC) (p < 0.001). At multivariate analysis, vitamin D deficiency (p < 0.01), HCC (p < 0.05), hospitalization (p < 0.001) and exposure to immunosuppressant agents (p < 0.05) were independent risk factors for infection at baseline. Conclusions: Vitamin D may play a role in the development of infections in patients affected by liver cirrhosis, and preventive strategies with vitamin D supplementation are to be evaluated in randomized controlled trials.